The early stages of Acacallis cyanea Lindl. (Orchidaceae) development under culture condition - L.A. Kovalskaya (Інтродукція Рослин, 1999)
The early development stages of seedling of Acacallis cyanea Lindl. – the endemic species of monotypical genus, distributed in the tropical South America, were studied. The seeds begin greening 2–2.5 months after seeding on the Knudson medium. The embryos of the germinating seeds have ovate-elongate a shape. By approximately 3–3.5 months the protocorm stage was reached. At that time the apical meristem with a single leaf primordium is available in the upper part of disk-shape protocorm. The first additional root was formed in 6–6.5 months; the first lateral bud was set in the axil of the fourth leaf at the age of approximately 8–9 months.